Factors affecting consumers' purchase behaviour of insurance policies. - Cheong, Kah Wye. (2008)
This study is conducted primarily to identify the factors that affect consumers' purchase behavior of life insurance products. It was a quantative survey research comprising of literature review and questionnaire. Various tests were use to analyse the data. From the results drawn, recommendatons were made to the industry.